Blood flow in the forearm in patients with Rheumatoid arthritis and healthy subjects under local thermotherapy - C. Mucha (AOSIS, 2002)
Objectives: Muscle blood flow in the forearm of patients with rheuma-toid arthritis and healthy volunteers following treatment with temperature increasingarm baths, mudpacks and short- or decimeter-wave diathermy was studied in thisinvestigation. The aim of the study was to find out the difference of reactive hyperemia between the different temperature methods as well as the influence on theconsensual reaction. Subjects: Eighty patients with rheumatoid arthritis, stage 3 according toSteinbrocker, as well as 80 healthy human subjects had been assigned numerically in the four therapy- and controlgroups. Patients with diseases influencing the peripheral blood flow were excluded. Design: Blood flow was measured by venous occlusion plethysmography in both forearms with the subjects lyingsupine. The application of the local heat therapies had been excluded on the left forearm. The forearm blood flow wasmonitored before heat therapy, directly after as well as in two further 10 minutes intervals. An analysis of variancewas used to determine the influence on blood flow of the response to the heat therapies in patients with rheumatoidarthritis and healthy subjects.Results: Under homogeneous starting conditions and a statistically uniformed high blood flow in rest the reactive values of blood flow on the left-hand side of application and the right consensual side showed high significant differencesbetween all methods of therapy. Differences between the patients and the healthy subjects only showed tendencies withpartially lower reactions, concerning the patients with rheumatoid arthritis. All methods of heat therapy caused a statistically provable consensual reaction that turned out smaller after diathermic methods. Here the post therapeuticreaction of the blood flow on the side of application was also lower or rather shorter. Conclusion: Greater differences of the blood flow in rest between the patients with rheumatoid arthritis and healthysubjects could not be observed. Temperature increasing arm baths and mud packs induced a provable higher increaseof local and consensual forearm blood flow than did diathermic methods. These results lead to the conclusion thatthere are differences in temperature distribution between the methods of therapy. Increasing arm baths and mud packsseem to have a stronger influence on the thermo reflexive skin perfusion.